Analisis Kesesuaian Asesmen Sumatif Akhir Semester Kelas X terhadap Capaian Pembelajaran dan Sebaran Ranah Kognitif pada Kurikulum Merdeka - Fitriana, Aisyah; Fianti (Unnes Physics Education Journal, 2024)
After the covid 19 pandemic, it had an impact on learning loss in the world of education. so that the Minister of Education, Culture, Research and Technology issued a decree to implement the independent curriculum as stated in the Decree of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia number 262 / M / 2022. Based on the implementation of the independent curriculum that has been running from 2022, there has not been much discussion about the suitability of the Final Semester Summative Assessment in terms of learning outcomes and the distribution of cognitive domains. The research to be carried out uses a type of qualitative research with a descriptive approach. The research will be carried out by determining the object of research on purpose, so the technique used is Purposive Sampling. The suitability of ASAS for Learning Outcomes (CP) which has high results with an average of 78% with various aspects of assessment including completeness of material, breadth of material, depth of material, accuracy of facts and concepts, accuracy of case examples, and suitability for scientific and contextual developments. Based on the distribution of cognitive domains when viewed from the percentage of each school, S01 has an even distribution and shows all levels of Low Order Thinking Skills (LOTS), Middle Thinking Skills (MOTS) and High Order Thinking Skills (HOTS) but dominant in MOTS. The percentage in S02 shows ASAS instruments that have HOTS levels. While in S03, it represents the level of LOTS dominant test items. the knowledge dimension that is often presented is the conceptual dimension, which shows that the question seeks to improve students' concept understanding. 1) It is necessary to measure the ASAS instrument with several peers, so that the effectiveness of the measuring instrument and correlation can be determined 2) Analysis needs to be carried out by identifying the ASAS test instrument based on the AKM test instrum ent 3) The results of the study can be developed by preparing the ASAS test instrument based on the AKM test instrument.